2004
DOI: 10.1038/sj.leu.2403613
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of NAD(P)H:quinone oxidoreductase is associated with an increased risk of infant acute lymphoblastic leukemia without MLL gene rearrangements

Abstract: NAD(P)H:quinone oxidoreductase 1 (NQO1) is a detoxification enzyme that protects cells against oxidative stress and toxic quinones. A polymorphism (C609T) in the gene produces in the heterozygous individuals (C/T) a reduction and in those homozygous for the variant allele (T/T) the abolishment of NQO1 protein activity. To assess whether NQO1 inactivating polymorphism (CT/TT) was a possible risk factor for infant acute lymphoblastic leukemia (iALL), we investigated the distribution of NQO1 genotype in 50 iALL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 14 publications
4
24
0
1
Order By: Relevance
“…Thus, the presence of the NQO1*2 polymorphism increased the risk of ALL only in males, but did not modify it in females. The increased risk of ALL conferred by NQO1*2 homozygosity found in this study is in agreement with some studies carried out in children with ALL; [31][32][33] however, other reports did not support these results.…”
supporting
confidence: 61%
“…Thus, the presence of the NQO1*2 polymorphism increased the risk of ALL only in males, but did not modify it in females. The increased risk of ALL conferred by NQO1*2 homozygosity found in this study is in agreement with some studies carried out in children with ALL; [31][32][33] however, other reports did not support these results.…”
supporting
confidence: 61%
“…In this context others studies have examined the NQO1*2 distribution according to MLL rearrangement status and have produced conflicting result. While Lanciotti et al [8] indicate that only the infantile ALL patients without MLL rearrangements had a significantly higher frequency of NQO1 genotypes associated with low/null activity enzyme. Wiemels et al [41] have found that low NQO1 activity genotypes (heterozygous CT or homozygous TT) were associated with ALL containing the MLL gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a proline to serine amino acid change at codon 187 that is associated with a loss of enzyme activity due to instability of the protein product. The NQO1*2 is associated with an increased risk of tobacco-related cancers and ALL [8,9,17,18]. Moreover other polymorphisms were detected in NQO1 gene and were associated with the modification of the enzyme activity like the NQO1*3.…”
Section: S Ouerhani (And)mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Some other cases of childhood ALL can be attributed to maternal exposures during pregnancy, 16,17 in which risk may be modulated by genetic polymorphisms of enzyme systems responsible for the metabolism of drugs or environmental xenobiotics. [18][19][20][21] However, variations in environmental exposures and genetic susceptibility can only account for small differences in childhood leukemia incidence rates, and do not explain the large differences (up to 10-fold) between HIC and some LIC (Table 2). Hence, the role of underdiagnosis and underreporting must be investigated.…”
Section: Sources and Quality Of Childhood Cancer Epidemiology Datamentioning
confidence: 99%